Multiple Intelligence in the Teaching and Learning Process: A Study of Howard Gardner's Thought, Challenges and Opportunities - Ahmad Walela (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
This study explores how the theory of Multiple Intelligence proposed by Howard Gardner can be effectively integrated into the teaching and learning process and the challenges faced in its implementation in various educational contexts. This study analyzes existing literature through a literature review approach to find common patterns, research gaps, and best practices in applying Multiple intelligence theory in the classroom. The literature analyzed includes journal articles, academic books, and research reports focusing on teachers' understanding of multiple intelligences, learning methods based on dual Intelligence, student responses to applying these methods, and varied and inclusive assessment systems. The study results show that although the theory of multiple intelligences has been widely recognized in education, its application still faces various challenges. Teachers' understanding of this theory is often limited, and many have been unable to adapt teaching methods to accommodate students' diverse intelligences optimally. In addition, more infrastructure and resources in schools are also needed to support kinesthetic, musical, and visual-spatial Intelligence. Nonetheless, previous research has shown that students respond positively when the learning methods used match their dominant Intelligence, which can improve their motivation, engagement, and learning outcomes. This literature review concludes that a more varied and inclusive learning approach must accommodate all student intelligences. In addition, Assessment and evaluation in education must be more flexible, considering non-cognitive intelligences that have been ignored in standardized tests. This study recommends increasing teacher training, providing supporting infrastructure, and developing a curriculum more adaptive to the diversity of students' Intelligence. The results of this study make an essential contribution to enriching the understanding of applying the theory of multiple intelligences and offering solutions to the challenges faced in modern education.